(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was conducted by retrieving data collected on the pre weaning mortality of Hampshire and Large Black piglets reared under intensive management at 30-Sow Teaching Unit of College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati. The finding revealed that the overall mortality of piglets up to pre-weaning age was 11.73 per cent in which Large Black piglets had more mortality (15.24%) than Hampshire breed (9.05%). Highest mortality was observed in winter season (20.67%) than summer (7.08%) season and also more in male piglets (12.47%) than female piglets (11.04%). More number of deaths were recorded in the month of March (30.46%) and September (12.64%) and at 2 to 5 weeks of age. Further analysis revealed that the various forms of enteritis (45.98%) were the major causes of pre-weaning mortality of piglets.